THE EFFECT OF WORK EXPERIENCE AND WORK FACILITIES ON THE PERFORMANCE OF EMPLOYEES OF THE AGRICULTURE AND PLANTATION SERVICE OF BATU BARA DISTRICT MEDIATED BY WORK MOTIVATION - Tiara Arinda; Putri Aulia; Rusmewahni; Cia Cai Cen (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine the Work Experience and Work Facilities on the Performance of Employees of the Agriculture and Plantation Service of Batu Bara Regency. The research method used is a quantitative method using the assistance of Smart PLS version 3.0 which is collected from the results of distributing questionnaires to Employees of the Agriculture and Plantation Service of Batu Bara Regency. The analysis method used in this study is to use an instrument test, namely a validity and reliability test. measurement model (outer model) namely validity test, reliability test, then structural model (inner model) including: coefficient of determination / r-square (r2), goodness of fit model and hypothesis test with t-statistic test and indirect effect test (indirect effect). The results of Smart PLS 3.0 in this study are Work Experience Affects Work Motivation, Work Facilities Do Not Affect Work Motivation, Work Experience Affects Performance, Work Facilities Do Not Affect Performance, Work Motivation Affects Performance, Work Experience Affects Performance Mediated by Work Motivation, Work Facilities Do Not Affect Performance Mediated by Motivation.